Effect of number and location of distant metastases on renal cell carcinoma mortality in candidates for cytoreductive nephrectomy: Implications for multimodal therapy. (19th November 2012) - Capitanio, Umberto; Abdollah, Firas; Matloob, Rayan; Salonia, Andrea; Suardi, Nazareno; Briganti, Alberto; Carenzi, Cristina; Rigatti, Patrizio; Montorsi, Francesco; Bertini, Roberto
Abstract : Objective: To test whether the combination of number and location of distant metastases affects cancer‐specific survival in patients with metastatic renal cell carcinoma. Methods: Overall, 242 metastatic renal cell carcinoma patients with synchronous metastases at diagnosis underwent cytoreductive nephrectomy at a single institution. Combinations of number and location of distant metastases were coded as: single metastasis and single organ affected, multiple metastases and single organ affected, single metastasis for each of the multiple organs affected, and multiple metastases for each of the multiple organs affected. Covariates included age, symptoms, performance status, American Society of Anesthesiologists score, hemoglobin, lactate dehydrogenase, tumor size, Fuhrman grade, T stage, lymph node status, necrosis, sarcomatoid features and metastasectomy at the time of nephrectomy. Results: The median survival was 34.7 versus 32.3 versus 29.6 versus 8.5 months for single metastasis and single organ affected, multiple metastases and single organ affected single metastasis for each of the multiple organs affected, and multiple metastases for each of the multiple organs affected patients, respectively. At multivariable analyses, the combination of number and location of distant metastases resulted in one of the most informative and independent predictors of cancer‐specific survival in metastatic renal cell carcinoma patients. The lung was the location with the highest rate of single organ affected (50.3% vs 35.1% in other sites; P  < 0.001). Considering only patients with a single metastasis, no statistically significantly different cancer‐specific survival rates were recorded ( P  > 0.3) among different metastatic organs. Conclusions: Among metastatic renal cell carcinoma patients undergoing cytoreductive nephrectomy, the combination of the number and location of distant metastases is a major independent predictor of cancer‐specific survival. Patients with multiple organs affected by multifocal disease are more likely to have poorer survival.